Diseño del nuevo edificio administrativo para la alcaldía del cantón San Pedro de Huaca en la provincia del Carchi - Arteaga Ger, Kevin Andrés (2024)
The project proposal is located in the canton of San Pedro de Huaca of the Province of Carchi\; as a requirement of a new building for the mayor's office, since the current property does not comply with standards of comfortable and architectural spaces of an administrative nature to provide a good service, in terms of public administrative management and the services that the municipal mayor's office offers to the users. According to the need that arises, an alternative is proposed to implement an administrative building that meets the need and demand of the citizens of the Canton of San Pedro de Huaca. The degree work on the Architectural Design of the Administrative Building for the San Pedro de Huaca Mayor's Office is under the line of research on architectural urban planning for developing territories\; whose main objective is to provide an administrative center that responds to the needs of the population and carries out its management activities. Similarly, it is developed as an architectural element that allows satisfying the administrative activities demanded by the area and the generation of a meeting point between the inhabitants of the same, where, the transmission of ideas and the expression of their cultural identity, be the protagonists. In this architectural project it is necessary to take into account the current paradigm of covid-19, which proposes an evolution in the design of office spaces or alternative work spaces and architecture must give an efficient response due to which is mainly aimed at citizen care, as well as the security of public spaces, especially those that are very frequent, architecture faces the challenge of designing them in order to comply with the maximum hygienic and sanitary conditions that prevent the possible spread of future epidemics. By executing the architecture of the building, it will respond to the problems presented by the current mayor-day building, improving its workspaces, relationship system and customer service areas, where the spatial configuration of the administrative building can encourage or discourage the social interactions of those who will use the entity. The relationship of the central idea of the design will be focused on an architectural, structural solution and with the urban environment of the canton, proposing an innovative design that is related to the urban landscape, using concepts of sustainability and bioclimatic principles in the generation of healthy, comfortable, efficient and productive spaces.